Metabolic profile of Holstein and crossbred Holstein x Jersey cows in the peripartum Perfil metabólico de vacas Holandês e mestiças Holandês x Jersey no periparto - Pelizza A.* (2019)
© 2019 Universidade Federal de Minas Gerais.The aim of this study was to determine and compare the metabolic profile of Holstein (H) and crossbred Holstein x Jersey (HxJ) on peripartum. For this, 24 cows were evaluated, 11 Holstein and 13 crossbreeds Holstein x Jersey. Weekly, venous blood sample were collected to determine concentration of glucose, beta-hydroxybutyrate (BHBA), total protein, albumin, aspartate aminotransferase (AST), creatine kinase (CK), total calcium, ionic calcium, magnesium, inorganic phosphorus and cholesterol. Body weight (BW) and body condition score (BCS) were also evaluated. The data were submitted to analysis of variance with repeated measures in time. Holstein cows presented higher BW, however, there was no difference for BCS in compare to crossbreed Holstein x Jersey cows. Tendency for higher serum concentrations of BHBA, AST and higher concentration of ionic calcium was observed in crossbreed cows in comparison to the Holstein. The energetic profile during the pre and postpartum transition period is similar for both genetic groups with higher concentrations of BHBA on the first week of lactation, however, with a tendency of higher serum concentrations of BHBA for crossbreed cows. Higher concentrations of ionic calcium were observed in crossbreed cows and higher concentrations of phosphorus in Holstein cows on peripartum. Holstein and Holtein x Jersey crossbreed cows have a similar energy profile during the pre and postpartum transition period in most of the indicators, except for calcium that was higher in crossbred cows and higher phosphorus in Holstein cows.